The effect of thymus extracts on phosphorus compounds in muscle and serum, and on serum calcium - Potop, Isabela (1966)
1. Thymectomy in young rabbits decreased the ATP content and increased the inorganic phosphate content of skeletal muscle. The serum calcium content was decreased, whereas the inorganic phosphate content was increased. 2. The administration of a lipid fraction (TL) or protein fractions (CIF and TP) of thymus extracts to thymectomized rabbits in short-term experiments increased the ATP content of muscle and decreased the inorganic phosphate contents of muscle and serum. Serum calcium content was increased. 3. The action of the thymus extract TP was specific only on the phosphate compounds, since the increase in serum calcium concentration was also caused by the control extract from muscle. The action of the extract TL is not specific, being paralleled by the action of a control extract from muscle.